2022
DOI: 10.1186/s12889-022-13329-z
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave and disability pension in a cohort of TMD-patients – The Swedish National Registry Studies for Surgically Treated TMD (SWEREG-TMD)

Abstract: Background Temporomandibular disorders (TMD) are common and affect approximately 10% of the adult population. TMD is usually associated with headache, pain in the masticatory muscles and/or the temporomandibular joint, clicking or crepitations during mandibular movement as well as painful and/or reduced mouth opening. This study aimed to investigate the level TMD-patients use social insurance benefits before and after their first time of diagnosis or first surgical event, compared to the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…A flowchart describing the recruitment process is presented in Figure 1 , which is a modified model of earlier published data. 29 The total study population consisted of 366 437subjects –33 315 cases and 333 122controls. In total, 120 individuals were excluded due to lack of index date or because of no possible match between the delivered data sets (see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart describing the recruitment process is presented in Figure 1 , which is a modified model of earlier published data. 29 The total study population consisted of 366 437subjects –33 315 cases and 333 122controls. In total, 120 individuals were excluded due to lack of index date or because of no possible match between the delivered data sets (see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The recruitment process and exclusion of study subjects are described in Fig 1 , which is a modified model of earlier presented data [ 4 ]. A total of 366 437 subjects were in the study population; of these, 33 315 cases and 333 122 controls were identified.…”
Section: Resultsmentioning
confidence: 99%
“… Flow-chart of the recruitment process, Sweden, 1998–2016, 33 315 cases and 333 122 controls. The figure is a modified model of earlier published data from SWEREG-TMD [ 4 ]. ICD-10: International Classification of Diseases 10 th Revision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations